Academy NExT: New and Exciting Transitions—A Residential Summer Program for Individuals With Disabilities. - Gallup, Jenn; Bocanegra, Joel; Miller, Connie; Page, Caralee; Bennett, Cory (Journal of Applied Rehabilitation Counseling, 2024)
Academy New and Exciting Transitions (NExT) was developed to serve participants who have an Individualized Education Program or 504 ages 15–21 in a residential program grounded in high-interest activities that include vocational and technical programs. The focus of the summer program was to develop communication, interview skills, and career exploration across a wide variety of vocational and technical careers that required minimal to substantial postsecondary training. Academy NExT is part of preemployment transition activities funded through a collaborative effort with Vocational Rehabilitation Services and the Workforce Innovation Opportunity Act. The article presents an overview of the program and outcomes based on qualitative findings.